2019
DOI: 10.1007/s11144-019-01609-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxy-steam reforming of methanol on copper catalysts

Abstract: The influence of copper content in the monometallic catalysts supported on the CeO 2 ·Al 2 O 3 binary oxide system on their catalytic activity and physicochemical properties in oxy-steam reforming of methanol was investigated. It was shown that activity and selectivity depends on the content of copper, its dispersion on the catalysts surface. It was confirmed that optimal copper content was 20 wt% of Cu. Copper catalysts with 20 wt% of Cu exhibited the highest methanol conversion and reaction rate value compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…On the other hand, the lack of the diffraction peak which is attributed to the CuO phase confirmed that the copper(II) oxide present on the catalyst surface was totally reduced in the studied condition (in a mixture of 5% H 2 -95% Ar at 300 • C for 1 h and reaction performed in OSRM process). In addition, the lack of metallic Cu and/or Ni particles in the diffraction patterns recorded for bimetallic catalysts may be also explained by the too small size of the crystallites to detect by the diffractometer [21,30]. The presence of other phases in the diffraction patterns were not confirmed by the X-ray diffraction technique.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…On the other hand, the lack of the diffraction peak which is attributed to the CuO phase confirmed that the copper(II) oxide present on the catalyst surface was totally reduced in the studied condition (in a mixture of 5% H 2 -95% Ar at 300 • C for 1 h and reaction performed in OSRM process). In addition, the lack of metallic Cu and/or Ni particles in the diffraction patterns recorded for bimetallic catalysts may be also explained by the too small size of the crystallites to detect by the diffractometer [21,30]. The presence of other phases in the diffraction patterns were not confirmed by the X-ray diffraction technique.…”
Section: Resultsmentioning
confidence: 95%
“…It is worth noting that 30% Cu-10% Ni/ZrO 2 ·Al 2 O 3 catalyst exhibited the highest hydrogen yield and the highest methanol conversion at 160 • C. However, the 30% Cu-10% Ni/ZrO 2 ·Al 2 O 3 catalyst exhibited lower selectivity to CO 2 production and higher selectivity toward CO formation compared to the 30% Cu-10% Ni/CeO 2 ·Al 2 O 3 and 30% Cu-10% Ni/ZnO·Al 2 O 3 systems. DME was not formed during the OSRM reaction in any of the investigated catalyst systems [21]. Lopez et al [10] also investigated Cu-Ni/ZrO 2 catalysts prepared via co-impregnation and subsequent impregnation methods and tested in the OSRM process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Time-of-flight secondary ion mass spectrometry (ToF-SIMS) results also confirmed a strong interaction of NiO with ZrO 2 in the case of the 20%Ni/ZrO 2 catalysts. The presence of selected NiZrO + ions emitted from the investigated surface of the 20%Ni/ZrO 2 system was detected.Catalysts 2020, 10, 346 2 of 21 purity hydrogen, which is directly related to the use of fuel cell technology [1][2][3][4][5]. Currently, the main technologies of the hydrogen production are based on the steam reforming of natural gas.…”
mentioning
confidence: 99%